Breaking the Cycle of Stunting: Development and Validation of Bunda Usir Stunting (Busita) Module and Media to Early Detection of Infant Stunting - Difa Nadila Utami; Sri Sumarni; Rozikhan Rozikhan (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
The prevalence of stunting in Indonesia is 24.4%, which is higher than the WHO average of 20%. One of the efforts that can be made to reduce stunting rates is the early detection of stunting in infants. An interactive e-booklet media called Busita was developed to provide practical early detection tools. The aim was to develop an interactive electronic booklet that provides content from the Busita module. The research method used in this study was Research and Development (RD). Validity testing was conducted using a group of Subject Matter Experts (SMEs), determined by the Content Validity Ratio (CVR) and Content Validity Index (CVI), and the USE Questionnaire for the media validated by five experts. The Busita module contains all essential materials inside, as proven by CVR and CVI values between 0 and 1, with an average of 0.8, which can be interpreted as very good and important. The interactive e-booklet Busita media obtained a feasibility assessment through expert validation with an average score of 84.09, covering four aspects of assessment: usefulness, ease of use, ease of learning, and satisfaction. This research also involved five cadres in a pilot study, and the results of the dependent t-test showed a p-value of 0.05. The module and the media have been shown to measure knowledge, attitude, and practice in the early detection of infant stunting.